Secrets - Deveraux, Jude (New York Atria Books, 2008)
Having harbored an unrequited love for a man she met in childhood, Cassandra impulsively breaks an engagement to become the now-widowed man's nanny, but realizes that her chance for winning his heart is threatened by dark secrets.
91286
Keywords: Unrequited love; Love stories